Multi-criteria evaluation of CO2 utilization options for cement plants using the example of Finland. (December 2021) - Zhaurova, Mariia; Soukka, Risto; Horttanainen, Mika
Highlights: Selection of most promising utilization options for CO2 captured from cement plants. Analysis of the CO2 utilization options via multiple criteria. Construction aggregates have the highest potential for constant storage of CO2 . Urea, urea-based products, and methane are the most promising shorter-term storage options. Abstract: Carbon capture and utilization (CCU) in valuable products offers the possibility of reducing unavoidable process emissions and offsetting process costs. The development of an effective CCU process requires a comprehensive feasibility study; however, it is not obvious which options are most appropriate for this. The current study proposes to identify the most promising CCU options by applying a set of criteria developed to represent different aspects of the utilization process: CO2 specific mass in the product, CO2 utilization potential (CUP), technology readiness level (TRL), resource use, requirements for CO2 quality, and health, safety, and environment (HSE) considerations. A detailed analysis of the most promising options identified in this paper will be carried out in a later study. Since few products provide permanent storage, this study separately evaluates options which have a shorter storage time, provided that the captured CO2 could be used instead of fossil feedstock in production processes. The evaluation was carried out for a Finnish cement plant, using data in the literature to describe and analyze the utilization options. The results show that no one option stands out as fully satisfying all criteria. Inorganic carbonates may offer the most effective alternative for long-term carbon storage while the most promising options among products with a shorter storage period are urea, its downstream products, and methane. The approach used in this study can be applied to other cement plants, adapting the criteria to the source properties and using local data.